Mucormycosis with peculiar aortic involvement in a child with acute lymphoblastic leukemia. (17th February 2020) - Biddeci, Giada; Antonello, Michele; Pizzi, Marco; Petris, Maria Grazia; Pillon, Marta; Donà, Daniele; Biffi, Alessandra; Putti, Maria Caterina
Abstract: Among fungal infection, mucormycosis is a rare but severe etiology in immunocompromised patients. Lung and sinus are the usual sites; the involvement of blood vessels is also described. The diagnosis is a real challenge, because blood tests (galactomannan, beta-D-glucan) are negative and the only diagnostic tool is usually the biopsy of the affected zone. Aortitis is rare and usually caused by bacterial infection, fungal etiology is unusual and only episodic cases are reported in literature. Medical therapy alone is usually not sufficient and debilitating surgical intervention is required. We report the case of a child affected by B precursor acute lymphoblastic leukemia, presenting a systemic fungal infection complicated by aortitis, probably due to Mucor. The patient developed fever and pneumonia during the Induction phase of chemotherapy. At the beginning, the infection was treated as bacterial and the diagnosis of Mucor infection was possible only after surgical intervention with histological analysis. Medical therapy (antifungal) was not sufficient alone to cure the infection and an urgent surgical intervention was required. This case underlines the challenge in the diagnosis of mucomycosis, that should be suspected in case of prolonged fever during aplasia, not responding to standard antibiotic and antifungal therapies. Mucor infection often require a combined intervention, both medical and surgical to cure the infection.